Desenvolvimento de um sistema de alertas para telemetria em dispositivos LPWAN - Silva, Matheus Moroso da (2021)
The topic of smart cities is currently the target of several studies, so much so that it is possible to find thousands of articles, publications and books on the subject. A technology that stands out in this medium is LoRaWAN, it allows the sending of data via radio waves, this in turn makes the messages to be sent over very large distances usually between 3 to 5 km, in addition to having a low power consumption and working in a range that has almost no interference from other devices. Studying previously carried out work, it was observed that there was a demand for internal sensing of devices and platforms or their telemetry itself, in order to solve this demand, the idealization and realization of this project emerged, which involves the development of a telemetry method through web application and notification through mobile app of LoRa devices, which presented efficient results and achieved the expected goals.